NGOs' Initiatives to Enhance Social Sustainability in the Supply Chain: Poverty Alleviation through Supplier Development Programs - Rodríguez, Jorge A.; Giménez Thomsen, Cristina; Arenas, Daniel; Pagell, Mark (The journal of supply chain management, 2016)
This research studies how nongovernmental organizations (NGOs) can implement supply‐management practices for poverty alleviation. The research inductively builds a theoretical framework from a nested case study, which includes one NGO and six firms implementing supplier development (SD) programs. The framework suggests a set of resources that enhance the social sustainability of the supply chain without creating trade‐offs between economic and social performance. This study has implications for decision‐makers in firms and NGOs about the type of resources they need to develop, and the characteristics they should seek when choosing partners for undertaking collaborative initiatives in social sustainability.